Diseases and economic performance: evidence from panel data - Mohamed Nor, Norashidah (Canadian Center of Science and Education, 2015)
The current study aims to estimate to what extent economic performance is affected by different types of diseases. Particularly, we intend to examine the impact of diseases such as dengue, TB and HIV on GDP per capita in selected Southeast Asian countries. The panel data analysis and cointegration estimation technique are adopted to achieve the objectives of the study. The findings reveal that the variables move together in the long-run, and the results confirmed by three cointegration tests: Johansen-Fisher, Kao and Pedroni. Additionally, the coefficients estimated using FMOLS and confirmed by DOLS. Most importantly, it has been shown that shocks to human capital (diseases) have a large adverse impact on economic performance, especially; dengue, TB and HIV. The second major finding was that the role of human capital is found to be very crucial expressed by education and labor. The findings of this study suggest that reduction of diseases can lead to considerable improvement in economic performance.